The Moderating Role of Board Independence in the Relationship Between CEO Tenure and Firm Performance in the Gulf Cooperation Council Countries - Alrizgan, Ahlam Mohammed; Atqa, Asna Abdullah; Ngalim, Siti Manisah (Advances in Social Sciences Research Journal, 2025)
This study examines the influence of CEO tenure on firm performance. It also investigates the moderating effect of board independence. The sample comprises publicly listed firms in the Gulf Cooperation Council Countries (GCC) stock markets over the period 2014–2023, and the analysis employs panel data techniques to test the proposed relationships. The empirical findings show that CEO tenure is positively and significantly associated with accounting-based performance (ROA), while no statistically significant relationship is found with market-based performance (Tobin’s Q). Robustness checks using ROE confirm the positive effect of tenure on accounting outcomes. The moderating role of board independence is evident in the case of ROA, where increased oversight diminishes the benefits of longer CEO tenure. For Tobin’s Q, however, the moderating effect of board independence is negative but not statistically significant. This study contributes evidence from an emerging-market environment by distinguishing between accounting and market results and by documenting the moderating role of board independence.